Profile of movement demands of national football players in Australia - Burgess, D. J.; Naughton, G.; Norton, K. I. (Journal of Science and Medicine in Sport, 2006)
Descriptive data on game movement demands of contemporary players in the Australian National Soccer League (NSL, now the A League) are lacking. The purpose of this study was to profile movement demands of NSL games and specifically analyse distance covered, time in various speed categories (e.g., walking, jogging, striding, etc.), number of sprint speed efforts and overall mean player speed. Video tapes of 45 players from the 2002 to 2003 NSL season were analysed for whole- and half-game movement patterns and game statistics using Trak Performance software. Bivariate and ANOVA statistics were used for between game halves and positional comparisons. Results showed no changes to the frequency and speed of high intensity demands in both halves of the game. However, a 14% slower overall speed in the second half of the game when compared with the first half was attributed to fewer observations of the low intensity movements (9.0% less walking and 12.4% less jogging) and more stationary periods. Engagement in game events such as kicking and passing was also 11.2% less frequent in the second versus first half of games. Position-specific results of higher movement speeds of midfield players (7.2 km h-1), compared with defenders (6.1 km h-1), agree with previous results from international professional leagues. The results provide position-specific directions for future conditioning drills and benchmark fitness requirements in high level soccer players. The results also highlight the challenge to ensure consistency of second-half performances for elite level soccer players in Australia.